Kinetics and Mechanism for Photolysis Ferrioxalate Complexes , in the Presence of Chromium (VI) in Aqueous Solutions. - Jraikuos, Hasan; Al- bani, Nabeel (Latakia University Journal -Basic Sciences Series, 2019)
In this work, the photolysis of ferrioxalate complexes attended to the photoreduction of hexavalent chromium has been studied kinetically and mechanistically in aqueous solutions, under UV/Visible irradiation . The results showed, that the iron(III) undergoes rapid photoreduction to iron(II), occompanied by oxidative degradation of oxalic ligands to carbon dioxide . Photochemically generated is readily reoxidized to by the present in the deaerated - system, thus the is reduced to at last. In addition, kinetics of the overall occurring photoreaction has been discussed, and its probable mechanism has been suggested under the experimental conditions employed.